A review on the soundscape indicators of parks / Josephine Siaw Ling Lee ... [et al.] - Lee, Josephine Siaw Ling; Hosni, Nafisa; Rusli, Noradila; Abdul Ghani, Nabila (Universiti Teknologi MARA, Perak, 2022)
Soundscape aids in reducing noise pollution, but is also a resource to create pleasing space at parks. Soundscape approach considers the perception and preference of people on environmental sound. However, different indicators vary based on their aims and context undertaken in a soundscape study. Therefore, a systematic review was carried out to identify and differentiate the indicators used to study the park soundscape. The main objective is to investigate how a park’s soundscape is measured and the strength and weaknesses of the indicators were compared. The review processes involved four stages which were identification, screening, eligibility, and inclusion. Review works of literature were identified in available open access journals with keywords of “soundscape”, “perception”, and “park”. Results showed that soundscape indicators could be differentiated into objective indicators such as sound pressure level and psychoacoustic measures; subjective indicators, including soundscape descriptors, acoustic evaluation, sound awareness, and sound preference. Subjective evaluation for soundscape was to study the quality of the environment, while objective and subjective evaluations investigated the relationship between soundscape and other factors. It was found that sound level is more straightforward due to its environment represented by psychoacoustic metrics. Soundscape descriptors rely on how people perceive the area. Acoustic comfort was used concerning noise or annoyance, while sound preference and awareness identified sound marks of the area. Therefore, a proper selection of physical metrics and subjective variables is needed to predict the environment-human interaction better.